The Revival Of Islam In Central Asia and The Rise Of Religious Fanaticism - Bahodir I. Daminov (Penerbit Jurnal Indonesia, 2024)
The article discusses the situation of Muslims in Central Asia during the Soviet Union era, the government’s policies on religion, the influence of political uses of religion within the USSR, and the impact of democratic freedoms and political diversity on religion. It also covers the historical rise of religious extremism.